Fractional variational calculus for nondifferentiable functions - Almeida, R.
We prove necessary optimality conditions, in the class of continuous functions, for variational problems defined with Jumarie's modified RiemannLiouville derivative. The fractional basic problem of the calculus of variations with free boundary conditions is considered, as well as problems with isoperimetric and holonomic constraints. © 2011 Elsevier Ltd. All rights reserved.